Interface for Barge-in Free Spoken Dialogue System Based on Sound Field Reproduction and Microphone Array. (8th January 2007) - Miyabe Miyabe, Shigeki Shigeki; Hinamoto Hinamoto, Yoichi Yoichi; Saruwatari Saruwatari, Hiroshi Hiroshi; Shikano Shikano, Kiyohiro Kiyohiro; Tatekura Tatekura, Yosuke Yosuke
Abstract : A barge-in free spoken dialogue interface using sound field control and microphone array is proposed. In the conventional spoken dialogue system using an acoustic echo canceller, it is indispensable to estimate a room transfer function, especially when the transfer function is changed by various interferences. However, the estimation is difficult when the user and the system speak simultaneously. To resolve the problem, we propose a sound field control technique to prevent the response sound from being observed. Combined with a microphone array, the proposed method can achieve high elimination performance with no adaptive process. The efficacy of the proposed interface is ascertained in the experiments on the basis of sound elimination and speech recognition.